2015
DOI: 10.1186/s12974-014-0233-0
|View full text |Cite
|
Sign up to set email alerts
|

NLRP1 inflammasome is activated in patients with medial temporal lobe epilepsy and contributes to neuronal pyroptosis in amygdala kindling-induced rat model

Abstract: BackgroundTemporal lobe epilepsy (TLE) is often characterized pathologically by severe neuronal loss in the hippocampus. Understanding the mechanisms of neuron death is key to preventing the neurodegeneration associated with TLE. However, the involvement of neuronal loss to the epileptogenic process has yet to be fully determined. Recent studies have shown that the activation of NLRP1 can generate a functional caspase-1-containing inflammasome in vivo to drive the proinflammatory programmed cell death termed ‘… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 32 publications
10
119
0
Order By: Relevance
“…High extracellular potassium opens pannexin channels leading to inflammasome activation in primary neurons and astrocytes [44]. Importantly, recent studies have showed inflammasome formation in different neuronal disorders including SCI [12,21,38,45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High extracellular potassium opens pannexin channels leading to inflammasome activation in primary neurons and astrocytes [44]. Importantly, recent studies have showed inflammasome formation in different neuronal disorders including SCI [12,21,38,45].…”
Section: Discussionmentioning
confidence: 99%
“…Several molecular biological processes, including changes of cell cycle-related gene expression, endoplasmic reticulum (ER) stress, glutamate excitotoxicity, free radical production, and inflammatory cytokine release contribute to neuronal death [1,[5][6][7][8]. Recently, inflammasome-associated neuronal programmed cell death, termed pyroptosis, has been shown to contribute to neuronal death in distinct neurological diseases [9][10][11][12]. Pyroptosis is induced by inflammasomes which consist of an apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), an adaptor protein, and caspase-1, an inflammatory cysteine-aspartic protease [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This lack of consensus and growing evidence of an immune/inflammatory component in epilepsy development makes it necessary to enlarge diagnostic and prognostic assessment to include other immunological biomarkers [16]. In response to this need, the involvement of different immune pathways in epilepsy pathogenesis is increasingly investigated in animal models and in humans [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[37] [38] In the same vein, artemisinins, a pannexin-I blocker, inhibit the NLRP-3 inflammasome activation to decrease glutamate and cytokine release. [ Oriaifo et al…”
Section: Introductionmentioning
confidence: 99%